2015
DOI: 10.1097/jcp.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the CYP3A4*22 Polymorphism and CYP2D6 Polymorphisms on Serum Concentrations of Aripiprazole, Haloperidol, Pimozide, and Risperidone in Psychiatric Patients

Abstract: Heterozygous presence of CYP3A4*22 does not increase serum levels of antipsychotics metabolized by both CYP3A4 and CYP2D6, whereas CYP2D6 polymorphisms do affect serum levels to a limited extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 59 publications
3
34
0
4
Order By: Relevance
“…After removing duplicates, we reviewed the remaining 185 articles in the form of title and abstract; 121 citations were excluded after the title and abstract screen. Subsequently, 55 articles were excluded following a full‐text screen, leaving 10 articles eligible for meta‐analysis . The general characteristics of the included studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing duplicates, we reviewed the remaining 185 articles in the form of title and abstract; 121 citations were excluded after the title and abstract screen. Subsequently, 55 articles were excluded following a full‐text screen, leaving 10 articles eligible for meta‐analysis . The general characteristics of the included studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The serum level of aripiprazole was significantly lower in EMs than in IMs (EM vs IM pooled SMD: −0.383; 95% CI: −0.735 to −0.031, P = 0.03; Figure B). We next conducted a sensitivity analysis of heterogeneity; when the study by van der Weide and van der Weide was omitted, the observed heterogeneity across the studies was clearly reduced ( I 2 = 0.0%, P Q = 0.60 > 0.5), while the difference in aripiprazole serum levels between CYP2D6 EMs and IMs remained significant (EM vs IM pooled SMD: −0.516; 95% CI: −0.743 to −0.289, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…В тоже время некоторые работы опровергают на-личие данной связи [9]. Замена гуанина на аденин в 1846 нуклеотидной паре гена CYP2D6 (CYP2D6*4, CYP2D6 1846G>T, rs3892097) приводит к наруше-нию сплайсинга и снижению активности изофер-мента CYP2D6, что должно приводить к замедлению скорости элиминации субстратов данного изофер-мента из организма [10].…”
Section: актуальностьunclassified
“…Галоперидол подвергается N-деалкилиро-ванию при участии CYP3A4, преобразу-ясь в 4-хлорофенил-4-гидроксипиперидин и p-фторбензоилпропионовую кислоту. Связь активности CYP3A4 со скоростью биотрансформации галоперидола, была показана в ряде исследований на больных шизофренией [2,3,5]. В тоже время не-которые работы опровергают наличие данной связи [1].…”
unclassified